Synthesis Of Chitosan-Multiwalled Carbon Nanotubes Nanocomposite For The Removal Of Remazol Black B Dye - Karthigesan, Velautham (Universiti Sains Malaysia, 2022)
Development of textile industries indirectly strived by the excessive application of attractive reactive dyes such as remazol black B (RBB). The presence of such dye in wastewater lead to water pollution which is a critical environmental issue to be handled. The purpose of this project is to synthesis a nanocomposite films made from composite of chitosan (CS) and/or polyvinyl alcohol (PVA) incorporated with multiwalled carbon nanotubes (MWCNTs) for the adsorption of RBB dye. Parameters such as CS and PVA weight content in the composite, adsorbent dosage and initial dye concentration were investigated throughout the batch adsorption study. The adsorption equilibrium time was 2880 minutes (48 hr). Pure CS film adsorption capacity and dye removal efficiency reached 10.96 mg/g and 91.796% respectively, higher than other CS-PVA blends and pure PVA. The addition of MWCNTs to the pure chitosan resulted in increased adsorption capacity of adsorbent. Increment in adsorbent dosage efficiently increases the RBB dye removal percentage however reduced the adsorption capacity of adsorbent. Increase in adsorption capacity can be observed when the initial dye concentration is increased. However, the initial dye concentration doesn’t affect the removal efficiency at the equilibrium but still contributes in the adsorption rate. Adsorption isotherm for both CS and CS-MWCNTs adsorption of RBB dye experimental data best fits the Temkin isotherm model (R2 = 0.9903 and R2 = 0.949) compared to Langmuir and Freundlich isotherm models. Pseudo-first order kinetic model fits best for CS and CS-MWCNTs adsorption of RBB dye experimental data, therefore provides a much accurate details on the adsorption kinetics than pseudo-second order kinetic model. The CS and CS-MWCNT films can be potentially used as an efficient adsorbent to adsorb RBB dye molecules in wastewater.